PENGARUH PATRIOTISME, KORUPSI DAN PUNGLI TERHADAP KEPATUHAN PERPAJAKAN DI KANTOR PELAYANAN PAJAK PRATAMA JAYAPURA - Mip Tahul Jannah; Linda Y. Hutadjulu; Andika Rante (Fakultas Ekonomi dan Bisnis, Universitas Cenderawasih, 2018)
The purpose of this study is to analyze the effect of Patriotism, Corruption and Illicit Payment on taxation compliance. The population in this study is the individual taxpayers who were enrolled in KPPPratama Jayapura. The number of samples in this study as many as 100 respondents in the area of Jayapura. Sampling was done by using multiple regression analysis. The statistic description, validity, reability, classic assumption test, the coefficient of determination (R ² test), and partial regression test (t test) were tested in this research. Based on the result of data analysis indicated that the Patrotism has significant affect on tax compliance. However, Corruption and illicit payments have no significant affect on the tax compliance